Atlantic Gandhi: Samudra Paar Mahatma - Natarajan, Nalini (Sage Publications, 2018)
Using the frames of diaspora theory, post-colonial discourse theory and the recent Atlantic turn in studies of resistance, this book brings into relief Gandhi's experience as a traveler moving from a classic colony, India, to the plantation and mining society of South Africa. The author forwards the argument that this move between different modes of production brought Gandhi into contact with indentured laborers, with whom he shared exilic and diasporic consciousness, and whose difficult yet resilient lives inspired his philosophy. It reads Gandhi's nationalistic (that is, anti-colonial) sentiments as born in diasporic exile, where he formed his perspective as a provincial subject in a multiracial plantation. The author's viewpoint has been inspired by the new analytic that has emerged in the last few decades: the Atlantic as an ocean that not just transported the victims of a greedy plantation system, but also saw the ferment of revolutionary ideas.